2010
DOI: 10.1158/1078-0432.ccr-10-0438
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Spectrum of Copy Number Aberrations in Pediatric High-Grade Gliomas

Abstract: Purpose: As genome-scale technologies begin to unravel the complexity of the equivalent tumors in adults, we can attempt detailed characterization of high-grade gliomas in children, that have until recently been lacking. Toward this end, we sought to validate and extend investigations of the differences between pediatric and adult tumors.Experimental Design: We carried out copy number profiling by array comparative genomic hybridization using a 32K bacterial artificial chromosome platform on 63 formalin-fixed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 34 publications
6
123
0
Order By: Relevance
“…[35][36][37] CDK6 is overexpressed in lymphoma, leukemia, glioma, glioblastoma, medulloblastoma, and cancers of squamous cells, salivary gland, bladder, pancreas and prostate. [38][39][40][41][42][43][44][45][46][47][48][49][50] In human prostate cancer cells, CDK6 has also been shown to bind androgen receptor and stimulate its activity in a kinase activity independent manner. 46 Blockage of CDK6 expression by microRNAs (miRNAs) has been shown to inhibit the proliferation of gliomas, medulloblastoma, prostate, bladder, gastric, hepatocellular, and lung cancer cells, indicating the significant role of CDK6 in the initiation and progression of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] CDK6 is overexpressed in lymphoma, leukemia, glioma, glioblastoma, medulloblastoma, and cancers of squamous cells, salivary gland, bladder, pancreas and prostate. [38][39][40][41][42][43][44][45][46][47][48][49][50] In human prostate cancer cells, CDK6 has also been shown to bind androgen receptor and stimulate its activity in a kinase activity independent manner. 46 Blockage of CDK6 expression by microRNAs (miRNAs) has been shown to inhibit the proliferation of gliomas, medulloblastoma, prostate, bladder, gastric, hepatocellular, and lung cancer cells, indicating the significant role of CDK6 in the initiation and progression of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated that the retinoblastoma (RB), p53 and RTK/PI3K/MAPK pathways are commonly disrupted in adult and paediatric glioblastomas through various genetic mechanisms (TCGA, 2008;Parsons et al, 2008). Nevertheless, our data has demonstrated that paediatric tumours show deregulation of these core pathways by copy number alterations in less than half the frequency of that reported for adult tumours: 25% RTK/PI3K/MAPK, 19% p53 and 22% RB versus 59%, 70% and 66%, for adult glioblastoma (Figure 1) (Bax et al, 2010;TCGA, 2008). Even though isolated cases presented clear genomic events linked to activation of the sonic hedgehog (SHH) and Notch pathways activation, there is no evidence of consistently targeted pathways in paediatric high-grade gliomas.…”
Section: High-grade Gliomamentioning
confidence: 64%
“…The first studies using large-scale genome profiling techniques to identify the key genetic alterations of brain tumours were only recently published (Kool et al, 2008;Parsons et al, 2008 Thompson et al, 2006). Nevertheless, the number of such studies have been increasing on the past few years, with the first studies in paediatric glioma patients starting to emerge (Barrow et al, 2011;Bax et al, 2010;Paugh et al, 2010;Qu et al, 2010;Schiffman et al, 2010;Zarghooni et al, 2010).…”
Section: Patterns Of Copy Number Changementioning
confidence: 99%
See 2 more Smart Citations